Silica-based colloid centrifugation enhances sperm quality in cockerel semen. Issue 1 (2nd January 2020) - Lin, H. L.; Chen, Y. H.; Lin, D. Y.; Lai, Y. Y.; Wu, M. C.; Chen, L. R.
ABSTRACT: 1. Percoll TM is one of the most widely used colloid for animal sperm preparation. The aim of this study was to evaluate whether Percoll TM colloid centrifugation could be practical to improve cockerel sperm quality, and to compare the effects of Percoll TM single layer centrifugation (SLC) and density gradient centrifugation (DGC) in order to obtain the most optimal protocol for cockerel semen. 2. In the experiment with Percoll TM SLC for fresh semen, an increase of motile sperm was seen after Percoll TM 80% SLC and 90% SLC was conducted, at levels of 28.8% and 30.2% respectively (P < 0.01). The increase of progressively motile sperm after Percoll TM 80% SLC and 90% SLC was 177.2% and 202.4% respectively (P < 0.01). Meanwhile, for semen stored at 4°C for 24 h, the increase of motile sperm after Percoll TM 70% SLC and 80% SLC was 41.2% and 44.0% (P < 0.01), and the increase of progressive sperm after Percoll TM 70% SLC and 80% SLC was 71.3% and 83.1% respectively (P < 0.01). Both the percentage of motile sperm and progressive sperm of the fresh and stored cockerel semen after appropriate Percoll TM SLC was significantly enhanced. 3. Sperm membrane integrity did not show any decrease after Percoll TM centrifugation compared with non-centrifuged semen, which suggested that the Percoll TM centrifugation treatment in this study did not cause damage to cockerel sperm membranes. 4. In the experiment regarding the comparison of Percoll TM SLC and DGC with fresh semen, the increase of motile sperm after Percoll TM 80% SLC, 90% SLC and 40%/80% DGC was 29.5%, 36.4%, and 25.0% respectively; and the increase of progressive sperm was 44.7%, 58.5%, and 54.7%, respectively. For semen stored at 4°C for 24 h, the increase of motile sperm after Percoll TM 70% SLC, 80% SLC and 35%/70% DGC were 41.2%, 44.0%, and 26.4%; and the increase of progressive sperm was 71.3%, 83.1%, and 43.7%, respectively. There were no significant differences between the increase of sperm motility after Percoll TM 80%, 90% SLC or Percoll TM 40%/80% DGC in fresh cockerel semen. There was no significant difference between Percoll TM 70%, 80% SLC and Percoll TM 35%/70% in stored cockerel semen. There was a tendency for sperm recovery rates with Percoll TM SLC to be higher than Percoll TM DGC, although this did not reach statistical significance in this study. 5. It was concluded that Percoll TM SLC was more suitable for cockerel sperm separation than Percoll TM DGC. The results suggested that Percoll TM 80% SLC was the most optimal procedure to separate fresh cockerel sperm and Percoll TM 70% SLC was the most optimal procedure to separate stored cockerel sperm. Percoll TM SLC is more simple, user-friendly and economical and less time-consuming than DGC for cockerel semen processing.